Variability in visualization of latent fingermarks developed with 1,2-indanedione–zinc chloride - Fritz, Patrick; Van Bronswijk, Wilhelm; Patton, Emma; Lewis, Simon (International Association for Identification, 2013)
Amino acid variability in sweat may affect the ability of amino acid-sensitive fingermark reagents to successfully develop all latent fingermarks within a large population. There has been some speculation that age, gender, or prior activity may be the cause for differences in the amino acid profile within a population.Latent fingermarks from 120 donors were collected and treated with 1,2-indanedione–zinc chloride. Grades were given to treated samples based upon their initial color and resultant luminescent properties. Degradation of developed prints over three years was also assessed by regrading all samples and comparing the results to the initial grade. Statistical analyses, such as the Mann-Whitney U test, revealed that there was a correlation between the grade and the age of the developed print, age of the donor, and the washing of hands. However, no link was found between the food consumption or gender of the donor and the grade.